Analisis kinerja Reksa Dana Saham Syariah di Indonesia Periode Tahun 2008-2012 (Menggunakan Metode Snail Trail) - , Isyana Candra Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The growth of syariah mutual fund is projected to continue to increase with the increasing number of investors who now begin to look to invest in syariah mutual considered as more profitable. This study aims to analyze the performance of syariah equity funds over the period January 2008 to July 2012. Analysis of the performance of syariah equity funds in this study used the approach Snail Trail. The research conducted in this thesis is limited to syariah equity funds listed on Bapepam LK. The samples used in this study were nine syariah equity funds actively expressed during the study period. The data used is the data on Monthly Net Asset Value (NAV) syariah equity funds and the value of the development of monthly Jakarta Islamic Index (JII) during the study period. The problems addressed in this study were the difference in the performance of their respective syariah equity funds. The performance difference appears from the analysis of movement patterns as snail trail levels of risk and return of syariah equity funds. After analyzing the syariah equity funds risk-return diagram, the majority of syariah equity funds are off to quadrant four (low risk-low return). Mutual funds, among others, Batavia Dana Saham Syariah, CIMB Islamic Equity Growth Syariah, Mandiri Investa Atraktif Syariah, Reksa dana Syariah BNP Paribas Pesona Amanah, and Trimegah Syariah Saham. While four other mutual funds, namely Cipta Syariah Equity Fund, Prulink Syariah Rupiah Equity Fund, Reksa dana PNM Ekuitas Syariah and Danareksa Indeks Syariah which strtaed off in the research in quadrant one and two. Some mutual funds experienced very volatile movements during the study period, one of which is Mandiri Investa Atraktif Syariah. This greatly affected investment managers in deciding new policies to improve the performance of mutual funds managed. The majority of syariah equity funds show a fairly steady movement over the study period which indicated a stable condition with a low fluctuation level and at the end of the period of performance of the mutual funds showing improvement, so that risk and return are obtained in accordance with the expectations of investors. Stable conditions also suggests hat fund managers have made the right policies, so as to maintain the stability of the performance of mutual funds.